Technology use to support knowledge creation process model in group problem solving / Alkhabra Saleh Abdullah M - Saleh Abdullah M, Alkhabra (2018)
This thesis proposed the technology use to support knowledge creation process model in group problem solving. The current technology use focuses on facilitating the dissemination of information sharing and knowledge, it lacks the support for knowledge creation process. In group problem solving, valuable tacit knowledge are created often not captured. Knowledge creation becomes more complex when it involve group of individual. A qualitative research approach is employed in this research. This research was carried out in three stages which are: (i) input, where the conceptual framework is developed; (ii) transformation, which involved data collection and analysis; (iii) output, where knowledge creation model is developed, and the mapping of technology use is proposed followed by the enhancement of the current platform, BENAR. the mapping of technology use and enhancement of the current platform BENAR. The research site was at Saudi Arabia, University of Ha’il specifically at the department of educational technology. Twelve respondent are chosen for data collection and eight experts are selected for model validation. The study discovered that knowledge creation process happens in four stages in group problem solving which are: (i) defining the problem, (ii) finding solutions, (iii) development of action plan and (iv) implementation and evaluation of the action plan. The technology use to support knowledge creation process model includes collaborative technology which are, group meetings, resources sharing, texting and drawing modules. This research contributed toward new knowledge through the development of a knowledge creation process model. which drew upon the insights of real users. The practical contribution is the development of HN Platform which can be used by the student to support knowledge creation process in group problem solving.